Heterologous artificial insemination (A.I.D.) - Ascenzo Palacio, Alberto (2015)
Artificial insemination, already accepted worldwide, at least from the strictly scientific point of view is in specific cases, a ral help the couple with fertility problems where the root cause lies in the male factor.